EVALUASI PENERAPAN PEDOMAN AKUNTANSI PESANTREN (PAP) PADA YAYASAN PONDOK PESANTREN AL-ANSHOR KOTA AMBON - Kurnia, Rosna; Kurnia, Wahyu Ismail (AMAL: Jurnal Ekonomi Syariah, 2020)
Pondok pesantren foundations are now more diverse in the education model being held. Not only limited to Islamic boarding schools, but formal education models such as elementary schools, madrasas, vocational education and so on make the Pondok Pesantren Foundation as one of the non-profit organizations that get more attention by the government and the private sector. Besides the rapid development, the Pondok Pesantren Foundation is still faced with a number of problems which are still difficult to overcome. One of them is financial management. On the basis of these problems, BI and IAI issued a PAP as a guideline for Indonesian pesantren in preparing their financial reports. For this reason, this study aims to evaluate to what extent the application of PAP at the Al-Anshor Islamic Boarding School Foundation in Ambon City. This research uses a qualitative approach. Collecting data using the trainggulation approach consisting of observation, interviews and documentation. The results showed that the Al-Anshor Islamic boarding school foundation has not implemented LAP. The model for recording the financial statements of the Al-Anshor Pondok Pasantren Foundation is only in the form of reports of inflows and reports of outflows.